Mortality prediction of the nutrient profile of the Chilean front-of-pack warning labels: Results from the Seguimiento Universidad de Navarra prospective cohort study - Bullón-Vela, Vanessa; Sayón-Orea, Carmen; Gómez-Donoso, Clara; Martínez, J. A.; Martínez-González, Miguel A.; Bes-Rastrollo, Maira (Frontiers in Nutrition, 2022)
Background and aims: The Front-of-Pack (FoP) nutrition labelling was established as a policy, empowering consumers to choose healthy food options for preventing diet-related noncommunicable diseases. This study aimed to evaluate the association between the nutrient profile underlying Chilean warning label score and all-cause mortality, and to conduct a calibration with the NutriScore in a large cohort of Spanish university graduates. Methods: This prospective cohort study analyzed 20,666 participants (8068 men and 12,598 women) with a mean (standard deviation) age of 38 years (± 12.4) from the SUN cohort. Dietary food intake was assessed by a validated semi-quantitative food-frequency questionnaire at baseline and after 10 years of follow-up. The warning label score was calculated by considering the threshold of nutrients (sugar, saturated fat, and sodium) and energy density per 100g/ml of product, as established by Chilean Legislation. Participants were classified according to quartiles of consumption of the warning label score: Q1 (≤5.0), Q2 (>5.0-7.1), Q3 (>7.1-9.8), and Q4 (>9.8). Time-dependent, multivariable-adjusted Cox models were applied. To compare the performance of the warning label score and Nutri-Score to predict mortality, we used the Akaike information criterion (AIC) and Bayesian information criterion (BIC) methods. Results: During a median of 12.2 years of follow-up, 467 deaths were identified. A higher score in the warning label values (lower nutritional quality) was associated with an increased risk of all-cause mortality [HR (95% CI) Q4 versus Q1: 1.51 (1.07 to 2.13); p-trend=0.010)] and cancer mortality [HR (95% CI) Q4 versus Q1: 1.91 (1.18 to 3.10); p-trend= 0.006)]. However, no statistically significant association was found for cardiovascular mortality. Furthermore, the warning label score and Nutri-Score exhibited comparable AIC and BIC values, showing similar power of prediction for mortality. Conclusions: A diet with a higher warning label score (>9.8 per day) was a good predictor of overall and cancer mortality in a large Spanish cohort of university graduates. Also, the warning label score was capable to predict mortality as well as the Nutri-Score. Our findings support the validity of the warning label score as a FoP nutrition labelling policy since it is able to highlight less healthy food products.